COVID-19 and changes in activity and treatment of ST elevation MI from a UK cardiac centre. (April 2021) - Chen, Yang; Rathod, Krishnaraj S.; Hamshere, Stephen; Choudry, Fizzah; Akhtar, Mohammed M.; Curtis, Miles; Amersey, Rajiv; Guttmann, Oliver; O'Mahony, Constantinos; Jain, Ajay; Wragg, Andrew; Baumbach, Andreas; et al.
Abstract: Background: The international healthcare response to COVID-19 has been driven by epidemiological data related to case numbers and case fatality rate. Second order effects have been less well studied. This study aimed to characterise the changes in emergency activity of a high-volume cardiac catheterisation centre and to cautiously model any excess indirect morbidity and mortality. Method: Retrospective cohort study of patients admitted with acute coronary syndrome fulfilling criteria for the heart attack centre (HAC) pathway at St. Bartholomew's hospital, UK. Electronic data were collected for the study period March 16th – May 16th 2020 inclusive and stored on a dedicated research server. Standard governance procedures were observed in line with the British Cardiovascular Intervention Society audit. Results: There was a 28% fall in the number of primary percutaneous coronary interventions (PCIs) for ST elevation myocardial infarction (STEMI) during the study period (111 vs. 154) and 36% fewer activations of the HAC pathway (312 vs. 485), compared to the same time period averaged across three preceding years. In the context of 'missing STEMIs', the excess harm attributable to COVID-19 could result in an absolute increase of 1.3% in mortality, 1.9% in nonfatal MI and 4.5% in recurrent ischemia. Conclusions: The emergency activity of a high-volume PCI centre was significantly reduced for STEMI during the peak of the first wave of COVID-19. Our data can be used as an exemplar to help future modelling within cardiovascular workstreams to refine aggregate estimates of the impact of COVID-19 and inform targeted policy action.